Severe head injuries in children - Semple, Patrick Lyle (Division of Neurosurgery, 2017)
The aim of this dissertation is to review the current literature on severe head injuries in children, with particular respect to epidemiology, clinical features and investigation, pathophysiology, management and outcome. In addition a retrospective study was carried out on severe head injuries at Red Cross War Memorial Children's Hospital. Finally, the findings of this study are discussed in the light of the experience of other neurosurgical and trauma centres. In this way similarities as well as features peculiar to our setting can be identified with the aim of improving the understanding and management of severe head injuries in children in the Western Cape.